Bridging Gaps in Wearable Technology for Exercise and Health Professionals: A Brief Review - Schumann, Moritz; Doherty, Cailbhe (International Journal of Sports Medicine, 2024)
The proliferation of wearable devices, especially over the past decade, has been remarkable. Wearable technology is used not only by competitive and recreational athletes but is also becoming an integral part of healthcare and public health settings. However, despite the technological advancements and improved algorithms offering rich opportunities, wearables also face several obstacles. This review aims to highlight these obstacles, including the prerequisites for harnessing wearables to improve performance and health, the need for data accuracy and reproducibility, user engagement and adherence, ethical considerations in data harvesting, and potential future research directions. Researchers, healthcare professionals, coaches, and users should be cognizant of these challenges to unlock the full potential of wearables for public health research, disease surveillance, outbreak prediction, and other important applications. By addressing these challenges, the impact of wearable technology can be significantly enhanced, leading to more precise and personalized health interventions, improved athletic performance, and more robust public health strategies. This paper underscores the transformative potential of wearables and their role in advancing the future of exercise prescription, sports medicine and health.
Keywords: accelerometer; photoplethysmography; sensors; artificial intelligence; sports medicine